2017
DOI: 10.1186/s12970-017-0177-8
|View full text |Cite
|
Sign up to set email alerts
|

International Society of Sports Nutrition Position Stand: protein and exercise

Abstract: Position statementThe International Society of Sports Nutrition (ISSN) provides an objective and critical review related to the intake of protein for healthy, exercising individuals. Based on the current available literature, the position of the Society is as follows:An acute exercise stimulus, particularly resistance exercise, and protein ingestion both stimulate muscle protein synthesis (MPS) and are synergistic when protein consumption occurs before or after resistance exercise.For building muscle mass and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
586
4
43

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(647 citation statements)
references
References 219 publications
(221 reference statements)
14
586
4
43
Order By: Relevance
“…Distribution and timing of protein intake is important and advice about suitable foods to be eaten before and after exercise and before sleep should be given. Adult literature suggests that 25 to 30 g protein per meal is optimal to enhance muscle protein synthesis . Ensuring protein is included in the meal prior to exercise may help reduce the risk of hypoglycemia during exercise .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distribution and timing of protein intake is important and advice about suitable foods to be eaten before and after exercise and before sleep should be given. Adult literature suggests that 25 to 30 g protein per meal is optimal to enhance muscle protein synthesis . Ensuring protein is included in the meal prior to exercise may help reduce the risk of hypoglycemia during exercise .…”
Section: Introductionmentioning
confidence: 99%
“…Milk based drinks are recommended as appropriate sources of protein and carbohydrate for enhancing muscle protein synthesis n sports nutrition literature. A further advantage of milk is its leucine content as this has been specifically associated with the ability to train, compete and recover …”
Section: Introductionmentioning
confidence: 99%
“…According to the British Nutrition Foundation (2015), protein requirements for regular participants in sports and exercise (like swimming/running or going to the gym on a regular basis) may be slightly higher than for the general sedentary population, in order to promote muscle tissue growth and repair. Also, the International Society of Sports Nutrition (Jäger et al, 2018) has stated that while it is possible for physically active individuals to obtain their daily protein requirements through the consumption of whole foods, supplementation is a practical way of ensuring the intake of an adequate quality and quantity of protein. Finally, the calorie content information has a direct relation to perceived healthiness that could exert a strong influence on behavior (Wegman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Only three studies demonstrated an increase in muscle mass in response to an exercise intervention . Adequate protein intake plays a major role on the promotion of muscle anabolism during exercise training . Thus, it might be hypothesized that, in those studies that reported no benefits on muscle mass, protein intake might have been insufficient (in terms of total amount and/or protein quality) to obtain beneficial effects.…”
Section: Discussionmentioning
confidence: 99%